Inhibition of melanoma cell-intrinsic Tim-3 stimulates MAPK-dependent tumorigenesis: tumor biology and immunology - Schatton, Tobias Franz Ioannis; Itoh, Yuta; Martins, Christina; Rasbach, Erik; Singh, Praveen; Silva, Mariana; Mucciarone, Kyla; Heppt, Markus V.; Geddes-Sweeney, Jenna; Stewart, Kate; Brandenburg, Anne; Liang, Jennifer; et al. (Cancer research, 2022)
T-cell immunoglobulin mucin family member 3 (Tim-3) is an immune checkpoint receptor that dampens effector functions and causes terminal exhaustion of cytotoxic T cells. Tim-3 inhibitors are under investigation in immuno-oncology (IO) trials, because blockade of T-cell-Tim-3 enhances antitumor immunity. Here, we identify an additional role for Tim-3 as a growth-suppressive receptor intrinsic to melanoma cells. Inhibition of melanoma cell-Tim-3 promoted tumor growth in both immunocompetent and immunocompromised mice, while melanoma-specific Tim-3 overexpression attenuated tumorigenesis. Ab-mediated Tim-3 blockade inhibited growth of immunogenic murine melanomas in T-cell-competent hosts, consistent with established antitumor effects of T-cell-Tim-3 inhibition. In contrast, Tim-3 Ab administration stimulated tumorigenesis of both highly and lesser immunogenic murine and human melanomas in T-cell-deficient mice, confirming growth-promoting effects of melanoma-Tim-3 antagonism. Melanoma-Tim-3 activation suppressed, while its blockade enhanced, phosphorylation of pro-proliferative downstream MAPK signaling mediators. Finally, pharmacologic MAPK inhibition reversed unwanted Tim-3 Ab-mediated tumorigenesis in T-cell-deficient mice and enhanced desired antitumor activity of Tim-3 interference in T-cell-competent hosts. These results identify melanoma-Tim-3 blockade as a mechanism that antagonizes T-cell-Tim-3-directed IO therapeutic efficacy. They further reveal MAPK targeting as a combination strategy for circumventing adverse consequences of unintended melanoma-Tim-3 inhibition.Tim-3 is a growth-suppressive receptor intrinsic to melanoma cells, the blockade of which promotes MAPK-dependent tumorigenesis and thus counteracts antitumor activity of T-cell-directed Tim-3 inhibition.
Gesehen am 22.08.2023